Tackling the Tuberculosis Epidemic in sub-Saharan Africa – unique opportunities arising from the second European Developing Countries Clinical Trials Partnership (EDCTP) programme 2015-2024 - Zumla, Alimuddin; Petersen, Eskild; Nyirenda, Thomas; Chakaya, Jeremiah (International journal of infectious diseases, 2015)
•Tuberculosis (TB) and HIV/AIDS remain two of the most common causes of death from an infectious disease worldwide.•Research and development is an important pillar of the WHO post-2015 global TB strategy.•TB imposes a huge burden on the already overstretched health services in sub-Saharan Africa (SSA). Research and development is an important pillar of the WHO post-2015 global TB strategy.•The past two decades has seen a renaissance of biomedical research, capacity development and training activities throughout SSA focused on malaria, HIV/AIDS, TB, parasitic infections and co-morbidities of communicable diseases with non-communicable diseases.•The establishment in 2003 of The European & Developing countries Clinical Trials Partnership (EDCTP), by the European Parliament and of the Council of the European Union was a major boost to these efforts for developing and sustaining local research, training and capacity development.•So successful was the first EDCTP programme that on December 2nd 2014 there was a historic launch of the second programme (EDCTP2) in Cape Town under the auspices of the European Commission and the South African Department of Science and Technology.•EDCTP2 investments into development of research and capacity in Africa through equitable north-south partnerships far surpasses that of any other and its laudable portfolio provides unique opportunities of leadership of scientific work fully devolving to Africa in TB/HIV and allow post-2015 TB targets to be achieved in SSA. Tuberculosis (TB) today remains a global emergency affecting 9.0 million people globally. The African Region bears the highest global TB/HIV burden and over 50% of TB cases in SSA are co-infected with HIV. An estimated 1.5 million died from the TB globally in 2013. A large majority of the 360,000 HIV-positive TB cases who died were from sub-Saharan Africa. Research and development is an important pillar of the WHO post-2015 global TB strategy. Advances in development of diagnostics, drugs, host-directed therapies, and vaccines will require evaluation under field conditions through multi-centre clinical trials at different geographical locations. Thus it is critically important that these evaluations are fully supported by all African governments and the capacity, trained staff and infrastructure required to perform the research and evaluations is built and made available. This viewpoint article reviews the opportunities provided by recently launched second programme (2015-2024) of the European & Developing Countries Clinical Trials Partnership (EDCTP2) for tackling the TB epidemic in Africa through its magnanimous portfolio. The unique opportunities provided by EDCTP2 for leadership of scientific research in TB and other diseases fully devolving to Africa are also covered.